MV benchmark estimation based on high-frequency test signal. (November 2016) - Zhang, Kangkang; Zhu, Yucai; Huang, Biao
Abstract : Highlights: Optimal test signal is introduced for control performance monitoring purpose. The minimum variance (MV) benchmark estimation without a prior knowledge of time-delay is proposed. A new method of time-delay estimation is developed by using high-order ARX model. Multivariable MV benchmark estimation is investigated. Abstract: This work is concerned with the minimum variance (MV) benchmark estimation without a prior knowledge of time-delay. The idea is to use a small high-frequency test signal in order to obtain the accurate time-delay estimation (TDE) result, then the MV benchmark can be calculated from the closed-loop data. Based on the analysis, a well designed test signal for control performance monitoring (CPM) is not only possible but also necessary, as it increases the identifiability of the closed-loop data without having a large effect on routine operation. A new TDE algorithm by using high-order auto regressive exogenous (ARX) model is proposed as well as the multivariable issue is investigated. Simulation examples of performance monitoring with low signal-to-noise ratio (SNR) are employed to demonstrate the effectiveness of the proposed method.